PENGAJIAN SEBAGAI PEMBENTUK KARAKTER ISLAMI BAGI GENERASI BANGSA DI DESA NGRECO KECAMATAN TEGALOMBO PACITAN - Suprapti Suprapti; Nurul Iman; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2019)
This study aims to find out how to carry out routine recitation, how to plan teenage recitation, and how the role of adolescents in efforts to shape Islamic character in Ngreco Village, Tegalombo District, Pacitan Regency. This study uses descriptive qualitative research, and data collection techniques in this study through interviews, observations and documentation. The results of the implementation of teenage study in the village of Ngreco Tegalombo Pacitan, in planning is different from formal schools in general. The process of implementing teenage recitation in the village of Ngreco Tegalombo Pacitan, in outline through several steps, namely: 1) The method used in character education is the method of memorizing and understanding verses of the Qur'an, Muhadloroh and stories. 2) The implementation technique is one week once, Sunday night Monday. 3) Teenage teaching materials, namely the Qur'an and religious material in general. Teenage study in Ngreco Village has a central role in the lives of adolescents in the community. The role includes the improvement of several aspects, teenage studies conducted by adolescents become a place of friendship that fosters the fertility of Islam. It is also a medium for conveying ideas that are beneficial to the Islamic character of adolescents. The results of the formation of Islamic character through teenage recitation in the village of Ngreco, Tegalombo Pacitan are first in terms of reading the Qur'an, second in terms of preaching, third in terms of worship and behavior.